2017
DOI: 10.1002/app.45074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of random and block copolymers of vinyl chloride and vinyl acetate by RAFT miniemulsion polymerizations mediated by a fluorinated xanthate

Abstract: Reversible addition–fragmentation chain transfer miniemulsion (co)polymerizations of vinyl acetate (VAc) and vinyl chloride (VC) are conducted in the presence of a fluorinated xthanate (X1). VAc miniemulsion polymerization can be well controlled by X1, and PVAc with small polydispersity index (PDI, <1.20) are obtained. X1 also shows well mediative effect to VC‐VAc miniemulsion copolymerization, while the PDI of VC‐VAc copolymer is greater than that of PVAc since a chain transfer rate to VC is greater than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…They found higher rates of polymerization but obtained slightly reduced control (e.g., M n 4200–17300, Đ ∼ 1.5) . Bao’s group , used a fluorinated xanthate (TDFCP) for RAFT polymerization of VC and found better control than CMPCD ( Đ ∼ 1.28, M n 7750, 55% conversion).…”
Section: Introductionmentioning
confidence: 99%
“…They found higher rates of polymerization but obtained slightly reduced control (e.g., M n 4200–17300, Đ ∼ 1.5) . Bao’s group , used a fluorinated xanthate (TDFCP) for RAFT polymerization of VC and found better control than CMPCD ( Đ ∼ 1.28, M n 7750, 55% conversion).…”
Section: Introductionmentioning
confidence: 99%
“…Abreu and co-workers 41,42 reported the synthesis of low-dispersity PVC making use of the dithiocarbamate, CMPCD (Figure 1), as a RAFT agent. Bao et al 43,44 reported the preparation of low-dispersity PVC, PVC-block-poly(vinyl acetate) and PVC-block-poly(N-vinylpyrrolidone), using the fluorinated xanthate TDFCP (Figure 1), as a mediator. We 19 found that RAFT polymerization of VC (1,4-dioxane, 45 °C, ABVN initiator) mediated by the xanthate HECP (Figure 1), provided low-dispersity PVC (Đ ∼ 1.20 for M n 3−11 K) with high end-group fidelity (calculated fraction of living xanthate ends (L) > 90%).…”
Section: Introductionmentioning
confidence: 98%
“…Even though the mechanisms of the xanthate process and the RAFT process are very similar, MADIX , is a terminology commonly used to describe the xanthate process and adopted by us in this work. Because of the lower reactivity of the CS bond of xanthates, they are designed to polymerize less activated (or fast propagating) monomers (LAM), such as vinyl acetate (VAc), ethylene, , vinylidene fluoride (VDF), , and VC. Nevertheless, they have also been used to polymerize more activated monomers (MAMs), such as styrene, , acrylic acid, , acrylates , and acrylamide , with relative success. This demonstrates the versatility of these chain transfer agents (CTAs), which has allowed access to the synthesis of controlled block copolymers using monomers with very disparate reactivities by simple sequential addition. , However, methyl methacrylate (MMA) polymerization is not controllable using xanthates, and for them, other RAFT agents such as fluorodithioformates , or switchable RAFT agents are required to access such controlled block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…They are used in a variety of commercial processes, including the manufacture of rayon, cellulose films, and textiles . Recently, the aqueous miniemulsion polymerization of VC using a fluorinated xanthate (3,3,4,4,5,5,6,6,7,7,8,8,8-tridecafluorooctyl-2-((ethoxycarbonothioyl)­thio) propanoate) and polymerization of VC in dioxane using 2-hydroxyethyl 2-(ethoxycarbonothioylthio) propanoate (HECP) were reported. In these works, the temperature employed was 45 °C or higher.…”
Section: Introductionmentioning
confidence: 99%